INSILICO DRUG DESIGN AND MOLECULAR DOCKING STUDIES OF NOVEL COUMARIN DERIVATIVES AS ANTI-CANCER AGENTS - Mehta, Simpi; Pathak, Seema R (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Cancer is the major worldwide problem. It arises due to uncontrolled growth of cells. In the present study a series of novel coumarin derivatives were designed and computationallyoptimized to investigate the interaction between designed ligands and 10 pdb files of five selected proteins. The objective here was to analyse in silico anticancerous activity of designed ligands to reduce cost and time for getting novel anticancerous drug with minimum side effects. Methods: Docking studies were performed to find outmaximum interaction between designed ligands and selected five proteins using Schrondinger software Maestro. Capecitabin has been used as reference compound. Structures of selected proteins were downloaded from protein data bank. Results: All the designed ligands showed mild to excellent binding with proteins.Most of the ligands exhibited better interaction compared to reference compoundcapacitabin with all pdb files. Some of designed ligands amongst (1-7) showed excellent docking score with all pdb files(2v5z, 2v60, 2v61) ofAmine oxidase. Conclusion: All the designed ligands were docked with ten pdb files of five different proteins and it was found that out of seven designed ligand, ligand 4 showed best binding (docking score -10.139 ) with pdb 2v5z of protein Amine oxidase. Docked ligand cavity of ligand 4 showed important hydrophobic/non polar residues such asIle199,Ile316,Trp119,Phe168,Ile198,Cys172,Tyr188,Tyr398,Tyr435,Phe343,Tyr60,Leu328,Leu171 and showed pi-pi interaction with Tyr326.Further wet lab studies are continued in our laboratory to confirm and find out efficiency and activity of target compounds. Keywords: Docking, Mono Amine Oxidase, Coumarin derivatives, Anticancerous activity, binding energy, Ramachandran Plot, Hydrophobic residue.